Heart rate response to orthostatic challenge in patients with dementia with Lewy bodies and Alzheimer's disease. Issue 1 (22nd October 2020) - Omoya, Rie; Miyajima, Miho; Ohta, Katsuya; Suzuki, Yoko; Aoki, Ai; Fujiwara, Mayo; Watanabe, Takafumi; Yoshida, Noriko; Suwa, Hiroshi; Kawara, Tokuhiro; Takahashi, Hidehiko; Matsushima, Eisuke; et al.
Abstract : Background: To elucidate the differences in autonomic dysfunction between dementia with Lewy bodies (DLB) and Alzheimer's disease using a simple and convenient method, we investigated the heart rate response to orthostatic challenge. Methods: Ninety‐seven people participated in this cross‐sectional study, and data from 26 DLB patients, 29 Alzheimer's disease patients, and 25 healthy elderly individuals were analysed. Participants underwent postural changes, including 5 min in a supine position, 1 min in a sitting position, and 3 min in an orthostatic position. Their heart rates were continuously recorded. Two heart rate variables were analysed as main outcomes: (i) the difference between heart rate in the sitting position and the peak heart rate within 15 s of orthostasis, defined as the 'early heart rate increase'; and (ii) the difference between the peak heart rate and the negative peak heart rate after this, defined as 'early heart rate recovery.' An early heart rate increase has been considered to reflect parasympathetic and sympathetic functions. Early heart rate recovery is considered to reflect parasympathetic function. We also investigated the frequency domains of resting heart rate variability. Results: A significant difference was observed across the three groups in early heart rate increase, and that of the DLB group was lower than that of the healthy control group. Early heart rate recovery also differed significantly across the three groups, and that of the DLB group was less than that of the healthy control group. In addition, the power of the low‐frequency component, which represents both sympathetic and parasympathetic activity, was significantly decreased in the DLB group compared to the Alzheimer's disease group. Conclusions: Impaired heart rate response to standing was detected in patients with DLB. Electrocardiogram is a convenient, non‐invasive method that might be useful as a subsidiary marker for DLB diagnosis and differentiation from Alzheimer's disease.